2023
DOI: 10.1111/1745-9125.12345
|View full text |Cite
|
Sign up to set email alerts
|

How to overcome the cost of a criminal record for getting hired

Abstract: Many theories emphasize how employment is protective against criminal recidivism, yet a criminal record is a major barrier for getting hired. We asked 591 managers to make hypothetical hiring decisions between two applicants whose key difference was the presence or absence of a criminal conviction. In addition, we randomly manipulated the education, references, wage, or experience of the applicant with the criminal record to identify which manipulations can offset the cost of the record on an applicant's proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Finally, we used an opt-in sample of American adults recruited via Qualtrics. We used Qualtrics because it provides samples that closely resemble the U.S. population (Boas et al, 2020), is increasingly used in social science research (Pew Research Center, 2019), and has been used successfully in prior criminological research (e.g., Moule et al, 2019;Santos et al, 2023). Further, given our interest in online behaviors and the perceptions of technology users, an online sample is appropriate for addressing the research questions in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we used an opt-in sample of American adults recruited via Qualtrics. We used Qualtrics because it provides samples that closely resemble the U.S. population (Boas et al, 2020), is increasingly used in social science research (Pew Research Center, 2019), and has been used successfully in prior criminological research (e.g., Moule et al, 2019;Santos et al, 2023). Further, given our interest in online behaviors and the perceptions of technology users, an online sample is appropriate for addressing the research questions in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has begun to investigate whether positive credentials-such as letters of recommendation, state-sanctioned certificates of rehabilitation, or trade certifications-can improve hiring outcomes for this population by neutralizing stigma associated with the negative criminal credential. Notable research in this area includes several audit studies in which researchers apply to real jobs as fictional applicants with criminal records and varying positive credentials (Cundiff, 2016;Decker et al, 2015;Leasure & Andersen, 2016, 2020Leasure & Kaminski, 2021;Lindsay, 2021;Ortiz, 2014), experimental surveys in which respondents are asked to make hypothetical hiring decisions about applicants with varying positive credentials (Cullen et al, 2023;Denver & DeWitt, 2023;DeWitt & Denver, 2020;Reich, 2017;Santos et al, 2023), and interviews with employers (Fahey et al, 2006). Initial evidence supporting the ability of positive credentials to improve hiring outcomes is mixed, although employer recommendations and positive work histories have shown particular promise (Cullen et al, 2023;Denver, 2020;DeWitt & Denver, 2020;Santos et al, 2023).…”
Section: Postrelease Employment and Positive Credentialsmentioning
confidence: 99%
“…Employer beliefs that colleges/universities are reliable, honest assessors of an applicant may be eroded or overridden if these same employers do not similarly believe in the honesty and reliability of prisons (for a discussion regarding honesty and reliability in the context of desistance signaling, see Reich, 2023). Santos et al (2023) found some evidence to suggest that the signaling potential of credentials can be complicated by their affiliation with prison. Although their research found that reference letters from former employers and professors effectively increased willingness to hire an applicant (for additional evidence supporting the impact of employer references, see also Denver & DeWitt, 2023;DeWitt & Denver, 2020), the effect was much smaller if the reference letter was provided by a prison reentry program supervisor and eliminated if the reference letter was provided by a probation or parole officer.…”
Section: Postsecondary Carceral Education-an Untested Positive Creden...mentioning
confidence: 99%
See 2 more Smart Citations